Re-personalization and stratification of hemophilia care in an evolving treatment landscape. Issue 1 (1st January 2019) - Hart, Daniel P.; Kessler, Craig M.; Aledort, Lou
ABSTRACT: Hemophilia therapeutics are evolving rapidly. Comprehensive care must also evolve to embrace this change. Online tools and guidelines are widely available to optimize prophylaxis with conventional clotting factor concentrates using an individual's predicted pharmacokinetic profile. Novel hemostatic agents (e.g. biphenotypic antibody) are also becoming widely available, with other agents with differing mechanisms of action in final stages of trial. Contemporary issues including challenges of prophylaxis; bleed treatment; laboratory monitoring and inhibitor risk/surveillance are summarized in this narrative review, focusing on how a re-personalization of education and treatment will be necessary to meet these challenges of the rapidly changing therapeutic landscape.